Didactics of physics in the Czech Republic: Trends, challenges and perspectives - Danuše Nezvalová (Pedagogická Orientace, 2011)
The goal of this paper is to determinate the concept didactics of physics and topoint out the changes in the approaches to didactics of physics from both the applicativeand integrative approach to the communicative and information-communicativeapproach. Didactics of physics is an interdisciplinary scientific discipline and thereforeits relation to general didactics and Shulman’s theory of pedagogical content knowledgeare studied. Attention is also paid to the research fields and on the perspectives of thenext development of didactics of physics.